INDIAN MEDICINAL PLANT TRIGONELLA FOENUM-GRAECUM: PHYTOCOMPOUNDS DETECTION AND PHARMACOLOGICAL STUDIES - Ahmad, Afaque; Verma, Hirday N; Dev, Kapil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Fenugreek (Trigonella foenum-graecum) is a medicinal plant of culinary origin commonly used as spice and vegetable. The present study was focused to identify the immunomodulatory applications of T. foenum-graecum. Methods: The presence of phytochemicals and many biological activities such as antioxidant, antibacterial, and antifungal and anti-inflammatory activities were identified by various standard protocol respectively. Results: The phytochemical analysis was flavonoids, alkaloids, phenols, etc., whereas no traces of carboxylic acid were found. Results showed that T. foenum-graecum aqueous and methanolic extract (TfgAE and TfgME) highly inhibited Escherichia coli (percentage mean growth inhibition [% MGI] of 77.012±1.732% and 78.428±1.448%) and least effective against Staphylococcus aureus (percentage MGI of 46.661±0.707% and 78.428±0.0076%), respectively. TfgAE, TfgME, and ascorbic acid demonstrated highest percentage 2,2-diphenyl-1-picrylhydrazyl radical scavenging of 94.19316±0.0047%, 94.7942±0.0050%, and 99.67775±0.0053% and lowest of 17.18339±0.0059%, 24.47114±0.0052%, and 61.81149±0.0046%, respectively. Ferric reducing antioxidant power assay of TfgAE and TfgME showed maximum of 1.0527±0.065 mM and 1.0067±0.041 mM and minimum value of 0.3027±0.052 mM and 0.275±0.057 mM, respectively, as compared to the ascorbic acid (1.1847±0.049 mM and minimal at 0.373±0.032 mM). TfgAE and TfgME showed anti-inflammatory activity with the highest inhibition of albumin denaturation of 44.93771±0.0071% and 39.14707±0.0068% and the lowest of 21.32969±0.0075% and 15.53905±0.0065%, respectively. The other assay revealed that TfgAE and TfgME demonstrated the highest proteinase inhibition of 29.94818±0.0071% and 74.337±0.0073% and the lowest of 14.47679±0.0082% and 25.327±0.0079%, respectively, at extract volume or amount of 1000 μl and 100 μl. Conclusion: Results showed T. foenum-graecum might act as strong natural antibiotic agent and antioxidant agent and can be used against inflammatory diseases.